Outcomes of Primary Trabeculectomy From Two Same-centre Cohorts 10 Years Apart. Issue 9 (September 2021) - Shiwani, Haaris A.; Naqvi, Salman; Cristian, Cristina; Au, Leon; Spencer, Anne F.; Fenerty, Cecilia H.; Mercieca, Karl J.
Abstract : Precis: Trabeculectomy can effectively lower intraocular pressure (IOP). A more junior surgeon profile is emerging. Mitomycin C (MMC) has replaced 5-fluorouracil (5-FU) intraoperatively with comparable success rates and a decrease in postoperative antimetabolite administration. Purpose: We compare 2-year outcomes for primary trabeculectomy in 2 cohorts, 10 years apart, performed at a large UK teaching hospital. Methods: Consecutive case series of trabeculectomies at Manchester Royal Eye Hospital between 2004-2005 (Cohort 1/C1) and 2014-2015 (Cohort 2/C2). Preoperative and postoperative data was collected for IOP outcomes and complications. Success was defined as IOP ≥6 and ⩽21, ⩽18, ⩽16, ⩽14, or ⩽12 mm Hg with/without a ≥20% decrease from preoperative IOP. The need for and absence of postoperative antihypertensive medication defined qualified and complete success, respectively. Results: A total of 186 cases were analyzed [52 (C1), 134 (C2)]. Mean preoperative IOP was 24±10 mm Hg (C1) and 21±7 mm Hg (C2) ( P =0.01). Overall, 34 (79%), 33 (77%), 33 (77%), 29 (67%), and 25 (58%) patients in C1 and 88 (70%), 82 (65%), 73 (58%), 64 (51%), and 40 (32%) patients in C2 achieved complete success for IOP ⩽21 mm Hg ( P =0.33), ⩽18 mm Hg ( P =0.22), ⩽16 mm Hg ( P =0.04), ⩽14 mm Hg ( P =0.09), or ⩽12 mm Hg ( P =0.004). Similarly, 43 (93%), 40 (87%), 40 (87%), 35 (76%), and 27 (59%) in C1 and 123 (98%), 116 (92%), 106 (84%), 87 (69%), and 58 (49%) in C2 achieved qualified success ( P =0.34, 0.37, 0.83, 0.48, and 0.19). In all, 32 (74%), 31 (72%), 31 (72%), 28 (65%), and 24 (56%) in C1 and 64 (51%), 63 (50%), 61 (48%), 54 (43%), and 39 (31%) in C2 achieved complete success with ≥20% reduction from preoperative IOP and IOP of ⩽21 mm Hg ( P =0.01), ⩽18 mm Hg ( P =0.02), ⩽16 mm Hg ( P =0.01), ⩽1 mm Hg ( P =0.02), or ⩽12 mm Hg ( P =0.006). By same definition, 37 (80%), 36 (78%), 36 (78%), 33 (72%), and 26 (57%) in C1 and 94 (75%), 93 (74%), 90 (71%), 75 (60%), and 58 (46%) in C2 achieved qualified success ( P =0.55, 0.69, 0.48, 0.20, and 0.30). Mean IOP at 2 years was 13±5 mm Hg (C1) and 13±4 mm Hg (C2) ( P =0.35). Overall, 62% had intraoperative 5-FU in C1; only MMC was used in C2 ( P <0.0001). Postoperative 5-FU was administered in 54% versus 22% in C1 and C2, respectively ( P <0.0001). Needling rates were not statistically different [42% (C1), 54% (C2)] ( P =0.22). Conclusions: Trabeculectomy is effective in lowering IOP with success comparable across various definitions. MMC replaced 5-FU as intraoperative antimetabolite resulting in reduced need for postoperative antimetabolite but not increased complications.